SMOKE-FREE ZONE POLICIES AND PNEUMONIA INCIDENCE AMONG INFANTS IN INDONESIA (ANALYSIS OF SECONDARY DATA FROM THE 2023 INDONESIA HEALTH SURVEY) - Adinda, Faiza; Siregar, Putra Apriadi; Arrazy, Syafran; Wasiyem, Wasiyem; Hidayat, Rahmat (Journal of Gender and Social Inclusion in Muslim Societies, 2025)
Indonesia remains one of the ASEAN countries that has not fully implemented a smoke-free zone policy (SFZ). SFZ policies can prevent air pollution that can cause pneumonia. The novelty of this study lies in its analysis of SFZ policies based on the level of regional regulations, namely Regional Regulations and Mayor/Regent Regulations, which are linked to pneumonia cases in infants, utilizing national data with a large sample size to provide empirical evidence as a basis for strengthening SFZ policy implementation in Indonesia. This study aims to determine the relationship between SFZ policies and pneumonia cases in infants in Indonesia. This study used a cross-sectional design. The study population consisted of 284,177 respondents, and the study sample consisted of 49,747 respondents. This study used the 2023 Indonesian Health Survey questionnaire as an instrument and used the chi-square test with JASP version 19 software for data analysis. The results of the study indicate that there is a significant relationship between the form of implementation of SFZ policies at the district/city level (p=0.045) and no significant relationship in the implementation of SFZ across provinces in Indonesia (p=0.162; PR=1.159), districts/cities that implemented SFZ (p=0.664; PR=1.059), the duration of SFZ implementation in districts/cities (p=0.269; PR=0.891), fathers' smoking behavior (p=0.867; PR=0.983), and mothers' smoking behavior (p=0.1; PR=1.938). It can be concluded that there is a significant relationship between the form of local regulations/mayor/regent regulations on SFZ and the incidence of pneumonia in infants in Indonesia with p=0.045. These findings emphasize the importance of the government's role in strengthening the implementation of SFZ policies through improved monitoring, enforcement, and integrated evaluation.  Policy strengthening can be achieved through regulations accompanied by strict sanctions, data-based monitoring by the Ministry of Health, and continuous education on the dangers of thirdhand smoke for parents.  In addition, the results also indicate that the gender of mothers as primary caregivers plays an important role in protecting infants from exposure to cigarette smoke. Therefore, empowering mothers through improved health literacy and social support is crucial to reducing the risk of pneumonia in toddlers. Districts/cities that do not yet have smoke-free policies are expected to formulate them immediately, while the wider community is expected to actively participate in supporting the implementation of smoke-free policies to protect toddlers from the dangers of smoking.